China's Motivation for Implementing the Belt and Road Initiative (BRI) in Indonesia within the Context of Southeast Asia (2015-2024) - Antika, Meli; Darmawan, Wawan Budi; Sumadinata, Widya Setiabudi (International Journal of Science and Society, 2025)
The Belt and Road Initiative (BRI) reflects Cina's grand ambition to strengthen its economic and geopolitical influence in the strategic Southeast Asian region including Indonesia through investment in transnational infrastructure. Cina sees Indonesia as a vital nation within the worldwide oceanic course due to the country's position that interfaces the Indian Sea and the Pacific Sea through the Strait of Malacca. This investigate employments a expressive subjective approach through different auxiliary sources such as official government reports, research reports, academic articles, sources and news media. The research aims to analyze the various factors behind Cina's motivation in launching BRI in the Southeast Asian region, especially in Indonesia. The knife in this research is the concept of national interest from Donald E. Nuchterlein to analyze more deeply the national interests underlying Cina's implementation of BRI in Indonesia. This study found that Cina's implementation of BRI in the Southeast Asian Region including Indonesia is to reduce dependence on foreign investment, utilize excess production capacity, secure energy supplies, maintain national defense stability, especially in maritime areas such as the South Cina Sea, and create a positive image in the eyes of the world by embracing BRI cooperation partner countries by emphasizing economic, cultural and non-intervention aspects.